Hướng dẫn viết về phim - Corrigan, Timothy (Tri thức, 2020)
Writing about the movies -- Beginning to think, preparing to watch, and starting to write -- Film terms and topics for film analysis and writing -- Six approaches to writing about film -- Style and structure in writing -- Researching the movies -- Manuscript form.